2017
DOI: 10.1016/j.bbrc.2016.12.127
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acid fish oil dietary supplements contain saturated fats and oxidized lipids that may interfere with their intended biological benefits

Abstract: Widely available fish oil dietary supplements (DS) may contain fats and oxidized lipids in addition to the beneficial omega-3 fatty acids (OM3FAs) for which they are purchased. Little is known about the potential biological effects of these oxidized lipids. The objective of this study was to assess the fatty acid content, oxidation products, and biological effects of leading fish oil DS available in the United States. Three top-selling fish oil DS in the US were included in this analysis. Fatty acid compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 34 publications
3
56
0
2
Order By: Relevance
“…Not infrequently, patients will substitute an over-the-counter (OTC) brand for a prescription version without informing physicians; contents of commercial brands vary appreciably, and often patients will not understand that the total marine oil in a bottle is not the same as the actual weights listed. This challenge has greater relevance than appreciated: when OTC brands were tested for the ability to inhibit copper-induced oxidation of human sdLDL in vitro, ≥30 other fatty acids were present [82]. In all, 10-14 different saturated species accounted for up to 36% of the total fatty acid content.…”
Section: Role Of Measuring N-3 Pufa Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not infrequently, patients will substitute an over-the-counter (OTC) brand for a prescription version without informing physicians; contents of commercial brands vary appreciably, and often patients will not understand that the total marine oil in a bottle is not the same as the actual weights listed. This challenge has greater relevance than appreciated: when OTC brands were tested for the ability to inhibit copper-induced oxidation of human sdLDL in vitro, ≥30 other fatty acids were present [82]. In all, 10-14 different saturated species accounted for up to 36% of the total fatty acid content.…”
Section: Role Of Measuring N-3 Pufa Levelsmentioning
confidence: 99%
“…The inclusion of studies that rely upon self-recall of n-3 product use, while rejecting those that rely upon n-3 PUFA levels, is particularly concerning. In the future, perhaps knowledge of n-3 PUFA levels will be considered as an advantage, not as a confounder to be ignored [14,23,[81][82][83][84][86][87][88]. Second, as discussed above, as the dual epidemics of obesity and T2D progress, glucose intolerance and atherogenic dyslipidemia follow, with increases in levels of TG, TRL, and cholesterol remnants.…”
Section: Recent Major Meta-analysesmentioning
confidence: 99%
“…Nevertheless, when given at similar doses, pharmaceutical and dietary-supplement omega-3 products affect the Omega-3 Index equivalently, 51 and oily fish intake has clearly been linked with reduced risk of CVD. 45 So even though there can be significant differences among encapsulated omega-3 formulations, 52 it is not unreasonable to assume that equivalent doses of EPA þ DHAdfrom whatever sourcedshould have similar effects on risk of CVD. 53…”
Section: Omega-3 Recommendationsmentioning
confidence: 99%
“…Nearly all contain both EPA and DHA and very few are available that claim to contain only EPA. Furthermore, multiple publications have raised concerns regarding the variability of omega‐3 content in dietary supplements as well as the quality and purity of these products (Kleiner, Cladis, & Santerre, ; Mason & Sherratt, ; Shim, Santerre, Burgess, & Deardorff, ; Truong, Johnson, & Gabriel, ; Tur, Bibiloni, Sureda, & Pons, ; Weitz, Weintraub, Fisher, & Schwartzbard, ; Zargar & Ito, ). For example, studies have shown that the actual concentrations of DHA and/or EPA in omega‐3 supplements may be far below or far in excess of the labeled amounts (Albert et al., ; Kleiner et al., ; Shim et al., ; Yi et al., ).…”
Section: Overview Of Omega‐3 Dietary Supplementsmentioning
confidence: 99%
“…For example, studies have shown that the actual concentrations of DHA and/or EPA in omega‐3 supplements may be far below or far in excess of the labeled amounts (Albert et al., ; Kleiner et al., ; Shim et al., ; Yi et al., ). In addition, omega‐3 dietary supplements are not “pure” and may contain contaminants and/or harmful/unwanted ingredients such as high concentrations of cholesterol, saturated fats, lipid peroxides, and oxidation products (Albert et al., ; Jackowski et al., ; Mason & Sherratt, ; Ritter, Budge, & Jovica, ; Truong et al., ; Tur et al., ; Weitz et al., ; Zargar & Ito, ). The presence of some of these ingredients may interfere with the intended health benefits of omega‐3 dietary supplements (Mason & Sherratt, ).…”
Section: Overview Of Omega‐3 Dietary Supplementsmentioning
confidence: 99%